Maintaining Religious Harmony through Predicting the Level of Lawlessness using Linear Regression - Adam Wardana; Dekis Aldamawan; M. Rival Ridautal Lillah; Mochamad Anwar Wirahadi; Mohamad Rasyid Ridho; Naufal Rizqullah (Asosiasi Khazanah Cendekia, 2023)
Crimes are basically committed due to low human faith and ultimately disrupt harmony, including inter-religious harmony. Therefore, the purpose of this study is to predict and determine the number of law violations that occurred in Yogyakarta Province in 2022 as a case study using a linear regression algorithm based on data ranging from 2012 to some of the data on law violations in 2022. The method used is the forecasting method in which the stages of data collection, data preprocessing, data modeling, and prediction processes are carried out. The accuracy of the linear regression model is 90%. However, there is a difference in accuracy between the training data and the test data. The training data gets an accuracy of 99% while the accuracy achieved by the test data is at 94% which is 5% lower than the training data. The prediction results using the linear regression model shows the number of the data on law violation that will occur in 2022 with correlation between crimes.